Reliability of a commercially available and algorithm-based kinetic analysis software compared to manual-based software - Carroll, K. M.; Wagle, J. P.; Sato, K.; DeWeese, B. H.; Mizuguchi, S.; Stone, M. H. (Sports Biomechanics, 2019)
There is a need for reliable analysis techniques for kinetic data for coaches and sport scientists who employ athlete monitoring practices. The purpose of the study was: (1) to determine intra- and inter-rater reliability within a manual-based kinetic analysis program; and (2) to determine test-retest reliability of an algorithm-based kinetic analysis program. Five independent raters used a manual analysis program to analyse 100 isometric mid-thigh pull (IMTP) trials obtained from previously collected data. Each trial was analysed three times. The same IMTP trials were analysed using an algorithm-based analysis software. Variables measured were peak force, rate of force development from 0 to 50 ms (RFD50) and RFD from 0 to 200 ms (RFD200). Intraclass correlation coefficients (ICC) and coefficient of variation (CV) were used to assess intra- and inter-rater reliability. Nearly perfect reliability was observed for the manual-based (ICC > 0.92). However, poor intra- and inter-rater CV was observed for RFD (CV > 16.25% and CV > 32.27%, respectively). The algorithm-based method resulted in perfect reliability in all measurements (ICC = 1.0, CV = 0%). While manual methods of kinetic analysis may provide sufficient reliability, the perfect reliability observed within the algorithm-based method in the current study suggest it is a superior method for use in athlete monitoring programs.